2007
DOI: 10.1073/pnas.0608563104
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of artificial visual percepts generated through thalamic microstimulation

Abstract: Electrical stimulation of the visual system might serve as the foundation for a prosthetic device for the blind. We examined whether microstimulation of the dorsal lateral geniculate nucleus of the thalamus can generate localized visual percepts in alert monkeys. To assess electrically generated percepts, an eyemovement task was used with targets presented on a computer screen (optically) or through microstimulation of the lateral geniculate nucleus (electrically). Saccades (fast, direct eye movements) made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 35 publications
2
133
0
Order By: Relevance
“…In the monkey lateral geniculate nucleus, stimulation currents of 40 A were detected by the animal (Pezaris and Reid, 2007). In the ventral caudal nucleus of humans, Patel et al (2006) reported microstimulation detection thresholds as low as 5 A.…”
Section: Discussionmentioning
confidence: 99%
“…In the monkey lateral geniculate nucleus, stimulation currents of 40 A were detected by the animal (Pezaris and Reid, 2007). In the ventral caudal nucleus of humans, Patel et al (2006) reported microstimulation detection thresholds as low as 5 A.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, SC BOLD responses could be mediated by antidromic stimulation of either retinal or cortical cells. Yet, a recent study in which the LGN of monkeys was stimulated during the execution of a sequential double-saccade task provided evidence arguing against such a thalamo-retino-tectal signal propagation 20 . Alternatively, SC BOLD may result from the activation of the Meynert cells of the deep cortical layers of V1 that project to SC 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Purkinje cells of the cerebellum and various neurons in the cerebral cortex and elsewhere have no known relationship to circadian photoreception. Phosphenes can also be produced by electrically stimulating the lateral geniculate nucleus (LGN) (Pezaris and Reid, 2007).…”
Section: Endogenous Photoperception Of Bioluminescent Biophotons By Nmentioning
confidence: 99%